Discovery of a Selective TRPM8 Antagonist with Clinical Efficacy in Cold-Related Pain - Andrews, Mark D.; af Forselles, Kerry; Beaumont, Kevin; Galan, Sebastien R. G.; Glossop, Paul A.; Grenie, Mathilde; Jessiman, Alan; Kenyon, Amy S.; Lunn, Graham; Maw, Graham; Owen, Robert M.; Pryde, David C.; et al. (ACS medicinal chemistry letters, 2015)
The transient receptor potential (TRP) family of ion channels comprises nonselective cation channels that respond to a wide range of chemical and thermal stimuli. TRPM8, a member of the melastatin subfamily, is activated by cold temperatures (<28 degrees C), and antagonists of this channel have the potential to treat cold induced allodynia and hyperalgesia. However, TRPM8 has also been implicated in mammalian thermoregulation and antagonists have the potential to induce hypothermia in patients. We report herein the identification and optimization of a series of TRPM8 antagonists that ultimately led to the discovery of PF-05105679. The clinical finding with this compound will be discussed, including both efficacy and its ability to affect thermoregulation processes in humans.